The transformation of state islamic higher education institutions into World-Class University: From globalisation to institutional values - Sudirman Sudirman; Ramadhita Ramadhita; Syabbul Bachri; Yayuk Whindari (Social Sciences and Humanities Open)
The competition among alumni in the job market has driven universities worldwide to strive for the title of World Class University (WCU). In Indonesia, some public and private universities have entered the global rankings. However, only two State Islamic Higher Education Institutions (SIHEI) have entered the world rankings. Various efforts have been made to achieve internationalisation, but these efforts are hindered by institutional and financial management autonomy. This study aims to analyze the strategies adopted by SIHEI to achieve World-Class University (WCU) status and investigate how the incorporation of institutional values can mitigate the negative impacts of internationalisation. This article is based on qualitative research using a descriptive approach. Research data were obtained from secondary sources and interview with authoritative figures. The findings indicate that SIHEI must transform into State Universities with Legal Entity Status (SULES) to overcome the challenges of achieving WCU status. This transformation should be accompanied by local values to mitigate negative effects, such as the commercialisation of education and the erosion of educational values. Universitas Islam Negeri Malang has integrated institutional values into their academic and non-academic management. These values play a crucial role in enhancing the spirituality, morality, and integrity of their academic communities.